Nr4a1 promotes renal interstitial fibrosis by regulating the p38 MAPK phosphorylation - Yilin Tao; Chengyuan Tang; Ju Wei; Yi Shan; Xi Fang; Ying Li (BMC, 2023)
Abstract Background Renal interstitial fibrosis (RIF) is a common pathway to end-stage renal disease regardless of the initial etiology. Currently, the molecular mechanisms for RIF remains not fully elucidated. Nuclear receptor subfamily 4 group A member 1(Nr4a1), a member of the NR4A subfamily of nuclear receptors, is a ligand-activated transcription factor. The role of Nr4a1 in RIF remains largely unknown. Methods In this study, we determined the role and action mechanism of Nr4a1 in RIF. We used unilateral ureteral obstruction (UUO) mice and transforming growth factor (TGF)-β1-treated human renal proximal tubular epithelial cells (HK-2 cells) as in vivo and in vitro models of RIF. A specific Nr4a1 agonist Cytosporone B (Csn-B) was applied to activate Nr4a1 both in vivo and in vitro, and Nr4a1 small interfering RNA was applied in vitro. Renal pathological changes were evaluated by hematoxylin and eosin and Masson staining, and the expression of fibrotic proteins including fibronectin (Fn) and collagen-I (Col-I), and phosphorylated p38 MAPK was measure by immunohistochemical staining and western blot analysis. Results The results showed that Nr4a1 was upregulated in UUO mouse kidneys, and was positively correlated with the degree of interstitial kidney injury and the levels of fibrotic proteins. Csn-B treatment aggravated UUO-induced renal interstitial fibrosis, and induced p38 MAPK phosphorylation. In vitro, TGF-β induced Nr4a1 expression, and Nr4a1 downregulation prevented TGF-β1-induced expression of Fn and Col-I and the activation of p38 MAPK. Csn-B induced fibrotic proteins expression and p38 MAPK phosphorylation, and moreover Csn-B induced fibrotic proteins expression was abrogated by treatment with p38 MAPK inhibitor SB203580. We provided further evidence that Csn-B treatment promoted cytoplasmic accumulation of Nr4a1. Conclusion The findings in the present study indicate that Nr4a1 promotes renal fibrosis potentially through activating p38 MAPK kinase.